Return-to-sports criteria used by professional team physicians in elite athletes after hip arthroscopy–a qualitative study - Pasurka, Mario; Szlufcik, Mike; Theodoropoulos, John; Betsch, Marcel (The physician and sportsmedicine, 2024)
Objectives: The purpose of this study was to explore currently utilized readiness to Return to Sport (RTS) criteria after Hip Arthroscopy (HA) used in elite athletes to gain novel insights into the RTS decision-making process of professional team physicians. The authors hypothesized that even among this group of highly specialized physicians, there exists variability of measures and criteria used to determine RTS after HA. Methods: A total of 15 qualitative semi-structured interviews with professional team physicians were conducted by a single trained interviewer. The interviews were used to identify team physician concepts and themes regarding the criteria used to determine RTS after HA. Themes and sub-themes were identified using a general inductive analysis and a coding process. A hierarchical approach in coding helped to link themes. Results: Four key themes and several subordinate themes were identified from the interviews that seem to influence the return to sports decision. The most important RTS criteria were muscle strength (especially symmetric hip strength and muscle bulk with low side-to-side variance compared to the contralateral side) followed by pain-free sport-specific activity (pain-free drill skills and play at a lower level), physical examination (with major emphasis on the absence of hip pain with a painless hip range of motion compared to the contralateral side), and functional testing (including full squats, Ober test, FABER test, and pain-free FADIR position). Conclusion: Besides objective findings, including muscle strength, we identified time after surgery as well as subjective findings, including absence of pain and feedback of clinical team members that influence RTS decision after HA. We showed that even among specialized professional team physicians, the main criteria to RTS in these categories were not consistent necessitating the further development of specific RTS guidelines.
CRIS-Team Scopus Importer:2025-02-04
Keywords: hip arthroscopy; Qualitative research; return to sports